Lithium carbonate / graphite composite material, lithium ion battery and preparation method of lithium carbonate / graphite composite material
By coating the lithium carbonate layer on the graphite surface and converting it into a lithium carbonate/lithium fluoride composite coating, the problems of irreversible capacity loss and deterioration of cyclic performance in lithium-ion batteries are solved, and higher battery efficiency and longer cycle life are achieved.
Patent Information
- Application Number
- CN202311252530.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-26
- Publication Date
- 2025-03-28
AI Technical Summary
The application of natural graphite in lithium-ion batteries has problems of irreversible capacity loss and deterioration of cycling performance, which is mainly due to structural damage caused by volume changes in the graphite layer structure during lithium embedding and deintercalation.
Using lithium carbonate/graphite composite material, a core-shell structure is formed by uniformly coating the lithium carbonate coating on the graphite surface, and converted into a lithium carbonate/lithium fluoride composite coating through high-temperature calcination to construct an artificial SEI film to alleviate irreversible lithium consumption.
The first Coulomb efficiency of graphite negative electrode materials is improved, the cycle life of the battery is extended, and the electrochemical performance is improved and the electrolyte is prevented through the synergistic action of lithium carbonate and lithium fluoride.
Smart Images

Figure BDA0004470736710000221
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery materials and relates to a lithium carbonate / graphite composite material, a lithium ion battery and a preparation method thereof. Background Art
[0002] Positive and negative electrode materials with excellent performance and high safety have always been the focus of lithium-ion secondary battery research. From the perspective of clean, environmentally friendly and sustainable energy, designing environmentally friendly materials with high power, high energy density, high operating voltage, low self-discharge and long cycle life has always been the direction of researchers' efforts. Lithium-ion batteries have shown great potential in sustainable energy due to their high energy density, but the market demand for energy density is getting higher and higher. In this context, people have invested a lot of energy to design a new sustainable, safe, environmentally friendly and inexpensive positive / negative electrode material.
[0003] Natural graphite has high capacity, high compaction density, and is relatively cheap, with cost and specific capacity advantages. Natural graphite is mainly used in small lithium batteries and general-purpose lithium batteries for electronic products. At present, with the continuous expansion of the power battery market, the comprehensive requirements for factors such as material cost, processing performance, energy density, cycle life, and fast charging rate have increased, and the performance requirements for natural graphite are getting higher and higher. The structure of natural graphite determines that the volume of graphite changes greatly during the lithium insertion and deinsertion process, resulting in the destruction of the graphite layer structure, which in turn causes a large irreversible capacity loss and a sharp deterioration in cycle performance.
[0004] Graphite is used as the negative electrode. When it comes into contact with the electrolyte, the electrolyte salt lithium hexafluorophosphate (LiPF6) is first reduced on the electrode surface to generate a certain amount of lithium fluoride (LiF) and lithium ethylene dicarbonate (LEDC). As the battery ages, LEDC will decompose and further react with the electrolyte to produce Li2CO3, lithium alcohol, LiF, CO2, etc. Some of these products are soluble and gaseous, which will increase the porosity of SEI and form a loose and porous structure. The electrolyte will continue to penetrate into it to decompose and produce new LEDC and LiF. Such a repeated process will lead to the continuous growth of the SEI film, and the content of inorganic components will gradually increase. At the same time, the SEI film will gradually evolve into a double-layer structure with a dense inner layer with more inorganic components and a dense outer layer with more organic components.
[0005] Generally speaking, the Li consumed by the SEI film is irreversible, resulting in a decrease in the first coulombic efficiency of the electrode. The first coulombic efficiency of the current commercial graphite anode is about 90%. x The initial efficiency is basically less than 80%. In order to improve the initial efficiency of negative electrode materials, pre-lithiation is an effective technical means. In short, without pre-lithiation, Li+ When the positive electrode is embedded in the negative electrode, some lithium is lost due to the irreversible capacity. At this time, the lithium available for de-lithiation and return to the positive electrode will be less than the embedded lithium, resulting in the initial efficiency being less than 100%.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] The object of the present invention is to provide a lithium carbonate / graphite composite material, a lithium ion battery and a preparation method thereof.
[0008] In order to achieve the above purpose, the following technical solutions are adopted:
[0009] The invention provides a lithium carbonate / graphite composite material, comprising graphite and a lithium carbonate coating layer coated on the surface of the graphite.
[0010] Further, based on the above technical solution of the present invention, the particle size of the graphite is 15-20 μm;
[0011] And / or, the graphite is graphite with a surface treated with carbon coating;
[0012] And / or, the thickness of the lithium carbonate coating layer is 8-10 nm;
[0013] And / or, the mass fraction of the lithium carbonate coating layer in the lithium carbonate / graphite composite material is 0.5-3.0%.
[0014] The present invention also provides a method for preparing the above lithium carbonate / graphite composite material, comprising the following steps:
[0015] (a) providing an aqueous solution containing an organic lithium compound;
[0016] (b) adding graphite to an aqueous solution containing an organic lithium compound, stirring and mixing to allow the organic lithium compound to be adsorbed onto the graphite surface, then performing solid-liquid separation, and drying the adsorbed graphite to obtain an organic lithium compound / graphite material;
[0017] (c) calcining the organic lithium compound / graphite material at high temperature under a protective atmosphere to obtain a lithium carbonate / graphite composite material.
[0018] Further, based on the above technical solution of the present invention, in step (a), the organic lithium compound includes lithium acetate and / or lithium oxalate;
[0019] And / or, in step (a), the mass concentration of the organic lithium compound in the aqueous solution containing the organic lithium compound is 1-5%;
[0020] and / or, in step (b), the mass ratio of the graphite to the organic lithium compound in the aqueous solution containing the organic lithium compound is 100:(1-5);
[0021] And / or, in step (b), the stirring and mixing time is 3-4 hours.
[0022] Further, based on the above technical solution of the present invention, step (b) includes the following steps:
[0023] (b1) adding graphite to an aqueous solution containing an organic lithium compound, stirring and mixing so that the organic lithium compound is adsorbed onto the surface of the graphite, to obtain a mixed solution A;
[0024] (b2) subjecting the mixed solution A to solid-liquid separation to obtain adsorbed graphite;
[0025] (b3) replacing the graphite with the adsorbed graphite and repeating step (b1) and step (b2) at least once, and then drying the obtained adsorbed graphite to obtain an organic lithium compound / graphite material;
[0026] And / or, in step (b), the drying comprises rotary evaporation drying.
[0027] Further, based on the above technical solution of the present invention, in step (c), the protective atmosphere includes argon or nitrogen;
[0028] And / or, the high temperature calcination temperature is 600-700°C, and the high temperature calcination temperature is kept for 4-6 hours.
[0029] The present invention also provides a negative electrode sheet, comprising a negative electrode active material;
[0030] The negative electrode active material includes the lithium carbonate / graphite composite material or the lithium carbonate / graphite composite material prepared by the preparation method of the lithium carbonate / graphite composite material.
[0031] The present invention also provides a method for preparing a lithium ion battery, comprising the following steps:
[0032] After assembling the positive electrode sheet, the separator and the negative electrode sheet, injecting the electrolyte, and then standing to allow the electrolyte to react with the negative electrode active material, so that the lithium carbonate coating layer in the lithium carbonate / graphite composite material is converted into a lithium carbonate / lithium fluoride composite coating layer to obtain a lithium ion battery;
[0033] Among them, the negative electrode sheet is the above-mentioned negative electrode sheet provided by the present invention, the electrolyte includes an electrolyte lithium salt and a solvent, and the electrolyte lithium salt includes LiPF6.
[0034] Further, based on the above technical solution of the present invention, the standing temperature is 40-60° C., and the standing time is 3-4 days;
[0035] and / or, the solvent of the electrolyte is a carbonate solvent, including at least one of ethylene carbonate, dimethyl carbonate, diethyl carbonate or ethyl methyl carbonate;
[0036] And / or, the mass fraction of LiPF6 in the electrolyte is 10-12%.
[0037] The present invention also provides a lithium ion battery, which is prepared by the above-mentioned lithium ion battery preparation method;
[0038] The negative electrode active material in the negative electrode sheet after reacting with the electrolyte includes a lithium carbonate / lithium fluoride / graphite composite material, and the lithium carbonate / lithium fluoride / graphite composite material includes graphite and a lithium carbonate / lithium fluoride composite coating layer coated on the surface of the graphite.
[0039] Compared with the prior art, the technical solution of the present invention has at least the following technical effects:
[0040] (1) The present invention provides a method for preparing a lithium carbonate / graphite composite material. The preparation method is simple to operate and has a stable process. The lithium carbonate / graphite composite material prepared by the preparation method has a core-shell structure, that is, the lithium carbonate is uniformly coated on the graphite surface.
[0041] (2) The present invention provides a method for preparing a lithium-ion battery, wherein a positive electrode sheet, a separator and a negative electrode sheet are assembled, and then an electrolyte is injected. The assembled battery is then allowed to stand, so that the lithium carbonate in the lithium carbonate / graphite composite material in the negative electrode sheet reacts with the LiPF6 in the electrolyte, so that the lithium carbonate coating layer is in situ converted into a lithium carbonate / lithium fluoride composite coating layer, that is, the graphite surface is coated with lithium carbonate and lithium fluoride at the same time, thereby realizing the construction of an artificial SEI film on the graphite surface and pre-lithiation treatment of the graphite. This can alleviate the irreversible lithium consumption caused by the formation of the SEI film on the surface of the graphite negative electrode material, improve the graphite first effect, and at the same time, through the synergistic effect of lithium carbonate and lithium fluoride, not only can the Li + diffusion, improve electrochemical performance, and prevent decomposition of the electrolyte.
[0042] (3) The present invention provides a lithium ion battery, which is prepared by the above-mentioned preparation method. In view of the advantages of the above-mentioned lithium ion battery preparation method, the prepared lithium ion battery has good electrochemical properties. DETAILED DESCRIPTION
[0043] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.
[0044] The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.
[0045] According to a first aspect of the present invention, a lithium carbonate / graphite composite material is provided. The lithium carbonate / graphite composite material comprises graphite and a lithium carbonate coating layer coated on the surface of the graphite.
[0046] In the present invention, the " / " in the lithium carbonate / graphite composite material means "and", i.e., a composite material formed by lithium carbonate and graphite. In the present invention, the lithium carbonate / graphite composite material is actually a core-shell structure, with graphite as the core and the lithium carbonate coating layer as the shell coated on the surface of the graphite core.
[0047] The lithium carbonate / graphite composite material can be used as a negative electrode active material to prepare lithium-ion batteries. During the subsequent assembly of lithium-ion batteries, the lithium carbonate / graphite composite material will react with LiPF6 in the electrolyte, and the lithium carbonate coating layer will be converted into a lithium carbonate / lithium fluoride composite coating layer in situ, so some performance parameters of the lithium carbonate / graphite composite material need to be further optimized.
[0048] As an optional embodiment of the present invention, the particle size of graphite is 15-20 μm, preferably 15.5-18.5 μm. Typical but non-limiting particle sizes are 15 μm, 15.5 μm, 16 μm, 17 μm, 18 μm, 18.5 μm, 19 μm or 20 μm and the numerical range between any two points.
[0049] The graphite can be pure graphite or graphite that has been surface-modified. As a preferred embodiment of the present invention, the graphite is graphite that has been surface-coated with carbon. After the carbon coating, the graphite surface will have many functional groups, such as hydroxyl groups, carboxyl groups, etc., which are conducive to the coating of the lithium carbonate coating layer on the graphite surface.
[0050] As an optional embodiment of the present invention, the thickness of the lithium carbonate coating layer is 8-10 nm, and a typical but non-limiting thickness is 8 nm, 8.5 nm, 9.0 nm, 9.5 nm or 10 nm.
[0051] As an optional embodiment of the present invention, the mass fraction of the lithium carbonate coating layer in the lithium carbonate / graphite composite material is 0.5-3.0%, preferably 0.56-2.72%. Typical but non-limiting mass fractions are 0.5%, 0.56%, 0.6%, 0.8%, 1.0%, 1.2%, 1.5%, 1.8%, 2.0%, 2.2%, 2.5%, 2.72%, 2.8% or 3% and the numerical range between any two points.
[0052] By further limiting the above parameters, the lithium carbonate coating layer is thinly and evenly coated on the graphite surface, which is beneficial to the full reaction of the lithium carbonate coating layer with LiPF6 in the electrolyte during the subsequent assembly of the lithium-ion battery, and can more effectively synthesize the lithium carbonate / lithium fluoride composite coating layer in situ, thereby effectively reducing the consumption of active lithium during the first charge and discharge process, improving the initial efficiency and specific capacity of the material, and extending the battery life.
[0053] According to a second aspect of the present invention, the present invention also provides a method for preparing the above-mentioned lithium carbonate / graphite composite material, comprising the following steps:
[0054] (a) providing an aqueous solution containing an organic lithium compound;
[0055] (b) adding graphite to an aqueous solution containing an organic lithium compound, stirring and mixing to allow the organic lithium compound to be adsorbed onto the graphite surface, then performing solid-liquid separation, and drying the adsorbed graphite to obtain an organic lithium compound / graphite material;
[0056] (c) calcining the organic lithium compound / graphite material at high temperature under a protective atmosphere to obtain a lithium carbonate / graphite composite material.
[0057] Specifically, the aqueous solution containing the organic lithium compound in step (a) is mainly a mixed solution formed by the organic lithium compound and water.
[0058] In step (b), graphite is mixed and stirred with an aqueous solution containing an organic lithium compound. Since graphite, especially graphite coated with carbon, has many functional groups on its surface, such as hydroxyl and carboxyl groups, and the functional groups of the organic lithium compound (for example, the organic lithium compound is lithium acetate, and its functional group is acetate; or the organic lithium compound is lithium oxalate, and its functional group is oxalate) interact with the hydroxyl and carboxyl groups, so that the organic lithium compound is fully adsorbed on the graphite surface, and then dried to obtain the organic lithium compound / graphite material.
[0059] It should be noted that the “ / ” in the organic lithium compound / graphite material means “and”, that is, a material formed by the organic lithium compound and graphite.
[0060] In step (c), the organic lithium compound / graphite material is calcined at high temperature to convert the organic lithium compound on the graphite surface into lithium carbonate (Li2CO3) to obtain a lithium carbonate / graphite composite material. Similarly, the " / " in the lithium carbonate / graphite composite material means "and", that is, a material formed by lithium carbonate and graphite.
[0061] The invention provides a method for preparing a lithium carbonate / graphite composite material. The preparation method is simple to operate and has a stable process. The lithium carbonate / graphite composite material prepared by the preparation method has a core-shell structure, that is, lithium carbonate is uniformly coated on the surface of graphite, which also provides a good basis for the subsequent conversion of a lithium carbonate coating layer into a lithium carbonate / lithium fluoride composite coating layer.
[0062] As an optional embodiment of the present invention, in step (a), the organic lithium compound includes lithium acetate and / or lithium oxalate.
[0063] As an optional embodiment of the present invention, in step (a), the mass concentration of the organic lithium compound in the aqueous solution containing the organic lithium compound is 1-5%, preferably 2-5%. Typical but non-limiting mass concentrations of the organic lithium compound are 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5% and the numerical range between any two points.
[0064] As an optional embodiment of the present invention, in step (b), before adding the graphite to the aqueous solution containing the organic lithium compound, the graphite may be dispersed to reduce the agglomeration of the graphite. There are many ways to disperse the graphite, such as using a dispersant (such as hexadecyltrimethylammonium bromide CTAB) for dispersion and stirring (such as magnetic stirring).
[0065] As an optional embodiment of the present invention, in step (b), the mass ratio of graphite to the organic lithium compound in the aqueous solution containing the organic lithium compound is 100:(1-5); a typical but non-limiting mass ratio is 100:1, 100:2, 100:3, 100:4 or 100:5.
[0066] As an optional embodiment of the present invention, in step (b), the stirring and mixing time is 3-4 hours. Typical but non-limiting stirring and mixing time is 3 hours, 3.5 hours or 4 hours.
[0067] By further limiting the concentration of the aqueous solution containing the organic lithium compound, the relative amount of graphite and the organic lithium compound and the stirring and mixing time, a uniform and thin lithium carbonate coating layer is adsorbed on the graphite surface.
[0068] As an optional embodiment of the present invention, in step (b), the stirring is magnetic stirring.
[0069] As an optional embodiment of the present invention, step (b) comprises the following steps:
[0070] (b1) adding graphite to an aqueous solution containing an organic lithium compound, stirring and mixing so that the organic lithium compound is adsorbed onto the surface of the graphite, to obtain a mixed solution A;
[0071] (b2) subjecting the mixed solution A to solid-liquid separation to obtain adsorbed graphite;
[0072] (b3) Repeating step (b1) and step (b2) at least once with the adsorbed graphite replacing the graphite, and then drying the obtained adsorbed graphite to obtain an organic lithium compound / graphite material.
[0073] It should be noted that after the mixed solution A is subjected to solid-liquid separation in step (b2), adsorbed graphite is obtained, and step (b3) is to repeat step (b1) using the adsorbed graphite instead of graphite, that is, the adsorbed graphite obtained in step (b2) is added to a newly prepared aqueous solution containing an organic lithium compound (whose concentration is the same as that of the aqueous solution containing an organic lithium compound during the first adsorption) for re-adsorption.
[0074] By further limiting the specific steps of step (b), the organic lithium compound can be fully and evenly adsorbed onto the graphite surface.
[0075] As an optional embodiment of the present invention, the stirring and mixing time in step (b1) is 3-4 hours (for example, 3 hours, 3.5 hours or 4 hours). A longer stirring time can obtain a uniform aqueous solution containing an organic lithium compound, and the organic lithium compound can fully react (act) with the functional groups on the surface of graphite, thereby being adsorbed onto the graphite surface.
[0076] As an optional embodiment of the present invention, the specific method of solid-liquid separation in step (b2) can be suction filtration.
[0077] As an optional embodiment of the present invention, the time of stirring and mixing again in step (b3) is 30-40 minutes. Typical but non-limiting stirring and mixing time is 30 minutes, 32 minutes, 35 minutes, 36 minutes, 38 minutes or 40 minutes and the numerical range between any two points.
[0078] As an optional embodiment of the present invention, in step (b3), step (b1) is repeated 1-3 times. Typically but not limiting, step (b1) is repeated once, twice or three times.
[0079] By further limiting the stirring and mixing time and the number of repetitions of step (b1), an appropriate amount of organic lithium compound is adsorbed on the graphite surface. If too much organic lithium compound is adsorbed on the graphite surface, excessive lithium carbonate will be coated on the graphite surface after subsequent calcination, resulting in an excessively high alkaline environment on the surface of the material, which will have an adverse effect on the cycle performance and safety of the battery; if the stirring and mixing time is too short, it is difficult for the organic lithium compound to form an effective and uniform coating layer on the graphite surface, and the pre-lithiation effect is not obvious, which is not conducive to the improvement of the electrochemical performance of the battery.
[0080] As an optional embodiment of the present invention, in step (b), drying includes rotary evaporation drying. Compared with the general oven drying method, rotary evaporation drying has a faster drying speed, can process a larger volume of sample at one time, and is heated more evenly.
[0081] As an optional embodiment of the present invention, in step (d), the protective atmosphere includes argon and / or nitrogen.
[0082] The temperature and time of high temperature calcination will affect the type of decomposition products of the organic lithium compound, the particle size and the degree of agglomeration, etc. As an optional embodiment of the present invention, the temperature of high temperature calcination is 600-700°C, and the holding time at the temperature of high temperature calcination is 4-6h. If the temperature of high temperature calcination is too high (higher than 700°C), the organic lithium compound may generate lithium oxide, which promotes particle agglomeration, grain enlargement, and specific surface area reduction, which is not conducive to the release and embedding of lithium ions in the material. If the temperature of high temperature calcination is too low (lower than 600°C), it is difficult to synthesize the lithium carbonate coating layer and a large amount of organic lithium compound remains, and the organic lithium compound may react with the electrolyte, thereby affecting the electrochemical performance of the battery. Therefore, the typical but non-limiting temperature of high temperature calcination is 600°C, 610°C, 620°C, 630°C, 640°C, 650°C, 660°C, 670°C, 680°C, 690°C or 700°C and the numerical range between any two points.
[0083] If the calcination (heat preservation) time is too short (less than 4 hours), only the surface organic lithium compound may decompose, while some organic lithium compounds have not yet decomposed. In the later battery preparation, the organic lithium compound will react with the electrolyte components, thereby affecting the electrochemical performance of the battery. If the calcination (heat preservation) time is too long (longer than 6 hours), it will also affect the particle size of the material, which is not conducive to the release and embedding of lithium ions in the material. Therefore, the typical but non-restrictive heat preservation time is 4 hours, 4.5 hours, 5 hours, 5.5 hours or 6 hours and the numerical range between any two points.
[0084] According to a third aspect of the present invention, the present invention further provides a negative electrode sheet, comprising a negative electrode active material;
[0085] The negative electrode active material includes the lithium carbonate / graphite composite material or the lithium carbonate / graphite composite material prepared by the preparation method of the lithium carbonate / graphite composite material.
[0086] As an optional embodiment of the present invention, the negative electrode sheet includes a current collector and an active material layer coated on the surface of the current collector, and the active material layer is mainly made of a negative electrode active material, a conductive agent and a binder.
[0087] In the present invention, the specific types of the current collector, the conductive agent and the binder are not limited, and any type of material commonly used in the art may be used.
[0088] As an optional embodiment of the present invention, the current collector includes copper foil or the like.
[0089] As an optional embodiment of the present invention, the conductive agent includes at least one of Super P, Ketjen black (KB), acetylene black, carbon nanotubes or graphene.
[0090] As an optional embodiment of the present invention, the binder includes at least one of carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyacrylic acid (PAA) or polyvinylidene fluoride (PVDF).
[0091] According to a fourth aspect of the present invention, the present invention also provides a method for preparing a lithium ion battery, comprising the following steps:
[0092] After assembling the positive electrode sheet, the separator and the negative electrode sheet, injecting the electrolyte, and then standing to allow the electrolyte to react with the negative electrode active material, so that the lithium carbonate coating layer in the lithium carbonate / graphite composite material is converted into a lithium carbonate / lithium fluoride composite coating layer to obtain a lithium ion battery;
[0093] Among them, the negative electrode sheet is the above-mentioned negative electrode sheet provided by the present invention, the electrolyte includes electrolyte lithium salt and solvent, and the electrolyte lithium salt includes LiPF6.
[0094] Specifically, in the preparation method of the lithium-ion battery, after injecting the electrolyte, the assembled battery is left to stand at a certain temperature so that the lithium carbonate in the lithium carbonate / graphite composite material in the negative electrode sheet reacts with the LiPF6 in the electrolyte. The specific reaction formula is as follows:
[0095] LiPF6+3Li2CO3=F2PO2Li+2CO2+4LiF
[0096] 4Li + +PO2F2 - +2H2O=Li3PO4+LiF+HF+3H +
[0097] Through the above reaction, the lithium carbonate coating layer in the lithium carbonate / graphite composite material is in situ converted into a uniform and dense lithium carbonate / lithium fluoride composite coating layer, that is, the graphite surface is coated with lithium carbonate and lithium fluoride at the same time, thereby realizing the construction of an artificial SEI film on the graphite surface and the pre-lithiation treatment of the graphite. This can alleviate the irreversible lithium consumption caused by the formation of the SEI film on the surface of the graphite negative electrode material, improve the first effect of graphite, and at the same time, through the synergistic effect of lithium carbonate and lithium fluoride, it can not only promote the Li + diffusion, improve electrochemical performance, and prevent decomposition of the electrolyte.
[0098] As an optional embodiment of the present invention, the temperature is 40-60°C, and the standing time is 3-4 days. Typical but non-restrictive standing temperatures are 40°C, 42°C, 45°C, 46°C, 48°C, 50°C, 52°C, 55°C, 56°C, 58°C or 60°C and the numerical range between any two points, and typical but non-restrictive standing times are 3 days, 3.5 days or 4 days, etc. The standing temperature cannot be too low (lower than 40°C), and the standing time cannot be too short, otherwise the reaction rate of lithium carbonate and the electrolyte lithium salt LiPF6 is slow, and it is difficult to form an effective coating layer of lithium fluoride. The standing temperature cannot be too high (higher than 60°C). Although the high temperature makes the generated lithium fluoride more, the side reactions that may be produced are also more, and its energy consumption is greater.
[0099] By further limiting the static temperature and time, a uniform and relatively thin coating film is formed on the graphite surface, which reduces the lithium source consumption without affecting the mobility of lithium ions. A stable SEI film must be a good Li + Conductor, only Li + At the same time, it should also act as an electronic insulator to prevent the electrolyte from taking electrons from the anode side to undergo a reduction reaction. If the structure of the SEI film is unstable, the electrolyte will decompose and consume faster.
[0100] As an optional embodiment of the present invention, the solvent of the electrolyte is a carbonate solvent, including at least one of ethylene carbonate, dimethyl carbonate, diethyl carbonate or ethyl methyl carbonate.
[0101] As an optional embodiment of the present invention, the mass fraction of LiPF6 in the electrolyte is 10-12%. Typical but non-limiting mass fractions of LiPF6 are 10%, 10.5%, 11%, 11.5% or 12%.
[0102] According to a fifth aspect of the present invention, the present invention further provides a lithium ion battery produced by the above-mentioned lithium ion battery production method.
[0103] The negative electrode active material in the negative electrode sheet after reacting with the electrolyte includes a lithium carbonate / lithium fluoride / graphite composite material, and the lithium carbonate / lithium fluoride / graphite composite material includes graphite and a lithium carbonate / lithium fluoride composite coating layer coated on the surface of the graphite.
[0104] The " / " in the lithium carbonate / lithium fluoride / graphite composite material of the present invention means "and", i.e., a composite material formed by lithium carbonate, lithium fluoride and graphite. The modified active material is actually a core-shell product, i.e., graphite is the core, and the composite coating layer of lithium carbonate and lithium fluoride is the shell coated on the surface of graphite.
[0105] In view of the advantages of the above-mentioned method for preparing a lithium-ion battery, the prepared lithium-ion battery has good electrochemical properties.
[0106] The present invention is further described in detail below in conjunction with specific examples and comparative examples. Those skilled in the art should understand that the examples are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Unless otherwise specified, the raw materials used in the present invention can be obtained from commercially available products. Among them, the grade of the carbon-coated natural graphite in the following examples and comparative examples is SG17-9995-96, the average particle size of the carbon-coated natural graphite is 17μm, and the specific surface area is 6.2m 2 / g.
[0107] Example 1
[0108] This embodiment provides a lithium carbonate / graphite composite material, comprising graphite and a lithium carbonate coating layer coated on the surface of the graphite;
[0109] The graphite is carbon-coated natural graphite, the thickness of the lithium carbonate coating layer is about 8nm, and the mass fraction of the lithium carbonate coating layer in the lithium carbonate / graphite composite material is about 1.12%.
[0110] The preparation method of the lithium carbonate / graphite composite material comprises the following steps:
[0111] (a) providing 100 mL of an aqueous solution containing an organic lithium compound (CH3COOLi), wherein the mass concentration of CH3COOLi is 3%;
[0112] (b) adding 100 g of carbon-coated natural graphite to an aqueous solution containing CH3COOLi (the mass ratio of carbon-coated natural graphite to CH3COOLi is 100:3), stirring and mixing for 3 h to allow CH3COOLi to be adsorbed onto the surface of the carbon-coated natural graphite, then performing solid-liquid separation, and subjecting the obtained adsorbed graphite to rotary evaporation drying to obtain a CH3COOLi / graphite material;
[0113] (c) placing the CH3COOLi / graphite material into a tubular furnace and calcining it at high temperature under a protective atmosphere at a temperature of 650°C. The material is kept at the high temperature for 4 hours to obtain a lithium carbonate / graphite composite material, wherein the thickness of the lithium carbonate coating layer in the lithium carbonate / graphite composite material is about 8 nm.
[0114] This embodiment also provides a method for preparing a lithium ion battery, comprising the following steps:
[0115] (a) Preparation of negative electrode sheet:
[0116] The active material, the conductive agent and the binder are mixed in a mass ratio of 96:1:3, and then mixed with a solvent (deionized water), and then homogenized in a rapid defoamer to obtain a negative electrode slurry, wherein the solid content of the negative electrode slurry is 40%;
[0117] Then, the negative electrode slurry is coated onto the current collector copper foil using a 200 μm scraper, and then dried, rolled, and sliced to obtain a negative electrode sheet;
[0118] Among them, the active material is the lithium carbonate / graphite composite material provided in the above embodiment, the conductive agent is Super P, the binder is CMC and SBR, and the mass ratio of CMC to SBR is 1:2.
[0119] (b) Battery assembly:
[0120] After assembling the positive electrode sheet (lithium metal sheet), the separator and the negative electrode sheet, an electrolyte is injected (the electrolyte in the electrolyte is LiPF6, the concentration of LiPF6 is 1 mol / L, the solvent includes ethylene carbonate (EC) and diethyl carbonate (DMC), the volume ratio of the two is 1:1, and then fluoroethylene carbonate (FEC, the amount is 5 vol.% of the total volume of the electrolyte) is added), and then it is left to stand in an oven at 40°C for 3 days to modify the active material in the negative electrode sheet, so that the lithium carbonate coating layer in the lithium carbonate / graphite composite material is in situ converted into a lithium carbonate / lithium fluoride composite coating layer to obtain a lithium ion button battery (CR2016).
[0121] Example 2
[0122] This embodiment provides a lithium carbonate / graphite composite material and a preparation method thereof, comprising the following steps:
[0123] (a) providing 100 mL of an aqueous solution containing an organic lithium compound, lithium acetate (CH3COOLi), wherein the concentration of CH3COOLi is 3%;
[0124] (b) specifically include:
[0125] (b1) adding 100 g of carbon-coated natural graphite to an aqueous solution containing CH3COOLi (the mass ratio of carbon-coated natural graphite to CH3COOLi is 100:3), stirring and mixing for 3 h to allow CH3COOLi to adsorb onto the surface of the carbon-coated natural graphite, to obtain a mixed solution A;
[0126] (b2) subjecting the mixed solution A to solid-liquid separation (suction filtration) to obtain adsorbed graphite;
[0127] (b3) adding the adsorbed graphite instead of graphite to the re-prepared aqueous solution containing CH3COOLi at a concentration of 3%, stirring and mixing again for 35 minutes, i.e. repeating steps (b1) and (b2) twice in sequence, so that CH3COOLi is effectively adsorbed on the graphite surface;
[0128] Then the obtained adsorbed graphite is subjected to rotary evaporation drying to obtain CH3COOLi / graphite material;
[0129] (c) placing the CH3COOLi / graphite material into a tubular furnace and calcining it at high temperature under a protective atmosphere at a temperature of 650°C and a holding time of 4 hours to obtain a lithium carbonate / graphite composite material, wherein the thickness of the lithium carbonate coating layer in the lithium carbonate / graphite composite material is about 8 nm.
[0130] This embodiment also provides a method for preparing a lithium-ion battery. Except for using the lithium carbonate / graphite composite material provided in this embodiment as the active material of the negative electrode sheet, the remaining steps and process parameters are the same as those in Example 1.
[0131] Example 3
[0132] This embodiment provides a lithium carbonate / graphite composite material and a preparation method thereof, except that in step (b3), the repetition of steps (b1) and (b2) for 2 times is adjusted to the repetition of steps (b1) and (b2) for 3 times, and the remaining steps and process parameters are the same as those in Example 2.
[0133] This embodiment also provides a method for preparing a lithium-ion battery. Except for using the lithium carbonate / graphite composite material provided in this embodiment as the active material of the negative electrode sheet, the remaining steps and process parameters are the same as those in Example 1.
[0134] Example 4
[0135] This embodiment provides a lithium carbonate / graphite composite material and a preparation method thereof, which are the same as those in Embodiment 2.
[0136] This embodiment also provides a method for preparing a lithium-ion battery, except that the above-mentioned lithium carbonate / graphite composite material provided in this embodiment is used as the active material of the negative electrode sheet, and in step (b), it is placed in an oven at 45°C for 3 days, and the remaining steps and process parameters are the same as those in Example 2.
[0137] Example 5
[0138] This embodiment provides a lithium carbonate / graphite composite material and a preparation method thereof, which are the same as those in Embodiment 2.
[0139] This embodiment also provides a method for preparing a lithium-ion battery, except that the above-mentioned lithium carbonate / graphite composite material provided in this embodiment is used as the active material of the negative electrode sheet, and in step (b), it is placed in an oven at 50°C for 3 days, and the remaining steps and process parameters are the same as those in Example 2.
[0140] Example 6
[0141] This embodiment provides a lithium carbonate / graphite composite material and a preparation method thereof, which are the same as those in Embodiment 2.
[0142] This embodiment also provides a method for preparing a lithium-ion battery, except that the above-mentioned lithium carbonate / graphite composite material provided in this embodiment is used as the active material of the negative electrode sheet, and in step (b), it is placed in an oven at 55°C for 3 days, and the remaining steps and process parameters are the same as those in Example 2.
[0143] Example 7
[0144] This embodiment provides a lithium carbonate / graphite composite material and a preparation method thereof, which are the same as those in Embodiment 2.
[0145] This embodiment also provides a method for preparing a lithium-ion battery, except that the above-mentioned lithium carbonate / graphite composite material provided in this embodiment is used as the active material of the negative electrode sheet, and in step (b), it is placed in an oven at 60°C for 3 days, and the remaining steps and process parameters are the same as those in Example 2.
[0146] Example 8
[0147] This embodiment provides a lithium carbonate / graphite composite material and a preparation method thereof, which are the same as those in Embodiment 2.
[0148] This embodiment also provides a method for preparing a lithium-ion battery, except that the above-mentioned lithium carbonate / graphite composite material provided in this embodiment is used as the active material of the negative electrode sheet, and in step (b), it is placed in an oven at 65°C for 3 days, and the remaining steps and process parameters are the same as those in Example 2.
[0149] Example 9
[0150] This embodiment provides a lithium carbonate / graphite composite material and a preparation method thereof, which are the same as those in Embodiment 2.
[0151] This embodiment also provides a method for preparing a lithium-ion battery, except that the above-mentioned lithium carbonate / graphite composite material provided in this embodiment is used as the active material of the negative electrode sheet, and in step (b), it is placed in an oven at 35°C for 3 days, and the remaining steps and process parameters are the same as those in Example 2.
[0152] Example 10
[0153] This embodiment provides a lithium carbonate / graphite composite material and a preparation method thereof, except that the concentration of the organic lithium compound in the aqueous solution containing the organic lithium compound in step (a) is adjusted from 3% to 5%, the thickness of the lithium carbonate coating layer in the lithium carbonate / graphite composite material is 9-10nm, and the remaining steps and process parameters are the same as those in Example 2.
[0154] This embodiment also provides a method for preparing a lithium-ion battery, except that the above-mentioned lithium carbonate / graphite composite material provided in this embodiment is used as the active material of the negative electrode sheet, and in step (b), it is placed in an oven at 55°C for 3 days, and the remaining steps and process parameters are the same as those in Example 2.
[0155] Embodiment 11
[0156] This embodiment provides a lithium carbonate / graphite composite material and a preparation method thereof. Except that the concentration of the organic lithium compound in the aqueous solution containing the organic lithium compound in step (a) is adjusted from 3% to 1%, the lithium carbonate coating layer in the lithium carbonate / graphite composite material is point-coated on the graphite surface, the coating is not very uniform, and the thickness of the formed lithium carbonate coating layer is also uneven. The remaining steps and process parameters are the same as those in Example 2.
[0157] This embodiment also provides a method for preparing a lithium-ion battery, except that the above-mentioned lithium carbonate / graphite composite material provided in this embodiment is used as the active material of the negative electrode sheet, and in step (b), it is placed in an oven at 55°C for 3 days, and the remaining steps and process parameters are the same as those in Example 2.
[0158] Example 12
[0159] This embodiment provides a lithium carbonate / graphite composite material and a preparation method thereof, except that the type of organic lithium compound in the aqueous solution containing the organic lithium compound in step (a) is replaced by lithium oxalate from CH3COOLi, the remaining steps and process parameters are the same as those in Example 2.
[0160] This embodiment also provides a method for preparing a lithium-ion battery. Except for using the lithium carbonate / graphite composite material provided in this embodiment as the active material of the negative electrode sheet, the remaining steps and process parameters are the same as those in Example 2.
[0161] Embodiment 13
[0162] This embodiment provides a lithium carbonate / graphite composite material and a preparation method thereof. Except that the temperature of high-temperature calcination in step (c) is adjusted from 650° C. to 700° C., the remaining steps and process parameters are the same as those in Example 2.
[0163] This embodiment also provides a method for preparing a lithium-ion battery. Except for using the lithium carbonate / graphite composite material provided in this embodiment as the active material of the negative electrode sheet, the remaining steps and process parameters are the same as those in Example 2.
[0164] Embodiment 14
[0165] This embodiment provides a lithium carbonate / graphite composite material and a preparation method thereof. Except that the temperature of high-temperature calcination in step (c) is adjusted from 650° C. to 580° C., the remaining steps and process parameters are the same as those in Example 2.
[0166] This embodiment also provides a method for preparing a lithium-ion battery. Except for using the lithium carbonate / graphite composite material provided in this embodiment as the active material of the negative electrode sheet, the remaining steps and process parameters are the same as those in Example 2.
[0167] Embodiment 15
[0168] This embodiment provides a lithium carbonate / graphite composite material and a preparation method thereof. Except that the temperature of high-temperature calcination in step (c) is adjusted from 650° C. to 720° C., the remaining steps and process parameters are the same as those in Example 2.
[0169] This embodiment also provides a method for preparing a lithium-ion battery. Except for using the lithium carbonate / graphite composite material provided in this embodiment as the active material of the negative electrode sheet, the remaining steps and process parameters are the same as those in Example 2.
[0170] Comparative Example 1
[0171] This comparative example provides a method for preparing a lithium ion battery, comprising the following steps:
[0172] (a) Preparation of negative electrode sheet:
[0173] The active material, the conductive agent and the binder are mixed in a mass ratio of 96:1:3, and then mixed with a solvent (deionized water), and then homogenized in a rapid defoamer to obtain a negative electrode slurry, wherein the solid content of the negative electrode slurry is 40%;
[0174] Then, the negative electrode slurry is coated onto the current collector copper foil using a 200 μm scraper, and then dried, rolled, and sliced to obtain a negative electrode sheet;
[0175] The active material is the carbon-coated natural graphite in Example 1, the conductive agent is Super P, the binder is CMC and SBR, and the mass ratio of CMC to SBR is 1:2.
[0176] (b) Battery assembly:
[0177] After assembling the positive electrode sheet (lithium metal sheet), the separator and the negative electrode sheet, the electrolyte is injected (the electrolyte in the electrolyte is LiPF6, the concentration of LiPF6 is 1 mol / L, the solvent includes ethylene carbonate (EC) and diethyl carbonate (DMC), the volume ratio of the two is 1:1, and then fluoroethylene carbonate (FEC, the amount is 5 vol.% of the total volume of the electrolyte) is added) to obtain a lithium-ion button battery (CR2016).
[0178] Comparative Example 2
[0179] This comparative example provides a method for preparing a lithium ion battery, comprising the following steps:
[0180] (a) Preparation of negative electrode sheet:
[0181] The active material, the conductive agent and the binder are mixed in a mass ratio of 96:1:3, and then mixed with a solvent (deionized water), and then homogenized in a rapid defoamer to obtain a negative electrode slurry, wherein the solid content of the negative electrode slurry is 40%;
[0182] Then, the negative electrode slurry is coated onto the current collector copper foil using a 200 μm scraper, and then dried, rolled, and sliced to obtain a negative electrode sheet;
[0183] The active material is the carbon-coated natural graphite in Example 1, the conductive agent is Super P, the binder is CMC and SBR, and the mass ratio of CMC to SBR is 1:2.
[0184] (b) Battery assembly:
[0185] After assembling the positive electrode sheet (lithium metal sheet), the separator and the negative electrode sheet, the electrolyte was injected (the electrolyte in the electrolyte was LiPF6, the concentration of LiPF6 was 1 mol / L, the solvent included ethylene carbonate (EC) and diethyl carbonate (DMC), the volume ratio of the two was 1:1, and then fluoroethylene carbonate (FEC, the amount was 5 vol.% of the total volume of the electrolyte) was added), and then it was left to stand in an oven at 40°C for 3 days to obtain a lithium-ion button battery (CR2016).
[0186] Comparative Example 3
[0187] This comparative example provides a lithium carbonate / graphite composite material and its preparation method is the same as that of Example 2;
[0188] This comparative example also provides a method for preparing a lithium-ion battery. Except that in step (b), the battery is not placed in an oven at 40° C. for 3 days, the remaining steps and process parameters are the same as those in Example 2.
[0189] Comparative Example 4
[0190] This comparative example provides a lithium carbonate / graphite composite material and its preparation method is the same as that of Example 2;
[0191] This comparative example also provides a method for preparing a lithium-ion battery, except that the electrolyte in the electrolyte in step (b) is replaced by lithium bis(fluorosulfonyl)imide instead of LiPF6, and the remaining steps and process parameters are the same as those in Example 2.
[0192] Comparative Example 5
[0193] This comparative example provides a method for preparing a lithium carbonate / graphite composite material, comprising the following steps:
[0194] 1.68 g of lithium carbonate and 100 g of carbon-coated natural graphite were ball-milled and mixed at a ball-to-material ratio of 2:1. The ball-milling time was 100 min and the ball-milling speed was 350 rpm to obtain a Li2CO3 / graphite composite material.
[0195] The thickness of the lithium carbonate coating layer of the Li2CO3 / graphite composite material obtained by the above method is about 0.5 μm, and the mass fraction of the lithium carbonate coating layer in the lithium carbonate / graphite composite material is 1.65%.
[0196] This comparative example also provides a method for preparing a lithium-ion battery. Except for using the lithium carbonate / graphite composite material provided in this comparative example as the active material of the negative electrode sheet, the remaining steps and process parameters are the same as those in Example 1.
[0197] Comparative Example 6
[0198] This comparative example provides a method for preparing a lithium carbonate / lithium fluoride / graphite composite material, comprising the following steps:
[0199] 100 g of carbon-coated natural graphite, 0.84 g of Li2CO3 and 0.59 g of LiF were ball-milled at a ball-to-material ratio of 2:1, the ball-milling time was 100 min, and the ball-milling speed was 350 rpm to obtain a lithium carbonate / lithium fluoride / graphite composite material.
[0200] This comparative example also provides a method for preparing a lithium ion battery.
[0201] (a) Preparation of negative electrode sheet:
[0202] The active material, the conductive agent and the binder are mixed in a mass ratio of 96:1:3, and then mixed with a solvent (deionized water), and then homogenized in a rapid defoamer to obtain a negative electrode slurry, wherein the solid content of the negative electrode slurry is 40%;
[0203] Then, a 200 μm scraper was used to apply the negative electrode slurry onto the current collector copper foil, and then dried, rolled, and sliced to obtain a negative electrode sheet; wherein the active material was the lithium carbonate / lithium fluoride / graphite composite material provided above in this comparative example, the conductive agent was Super P, the binder was CMC and SBR, and the mass ratio of CMC to SBR was 1:2.
[0204] (b) Battery assembly:
[0205] After assembling the positive electrode sheet (lithium metal sheet), the separator and the negative electrode sheet, the electrolyte is injected (the electrolyte in the electrolyte is LiPF6, the concentration of LiPF6 is 1 mol / L, the solvent includes ethylene carbonate (EC) and diethyl carbonate (DMC), the volume ratio of the two is 1:1, and then fluoroethylene carbonate (FEC, the amount is 5 vol.% of the total volume of the electrolyte) is added) to obtain a lithium-ion button battery (CR2016).
[0206] In order to compare the technical effects of the above embodiments and comparative examples, the following experimental examples are specially designed.
[0207] Experimental Example 1
[0208] The cycle performance and rate performance of the lithium ion batteries prepared in each embodiment and comparative example were tested, and the specific results are shown in Table 1. The cycle and rate tests were performed according to the following steps:
[0209] Cycle test: discharge at constant current to 0.01V; let stand for 120s; charge at constant current to 2.0V; let stand for 120s; terminate the program after 100 cycles. The current density set in this experiment is 100mA / g.
[0210] First cycle charging capacity test: After power on, let it stand for 2 hours, first discharge at a constant current of 0.1C to 0.01V, 0.08C to 0.005V, 0.05C to 0.005V, 0.02C to 0.005V, let it stand for 10 minutes, then charge at a constant current of 0.1C to 1.5V.
[0211] Table 1
[0212]
[0213] It can be seen from the data in Table 1 that the performance of the lithium ion battery prepared by using the lithium carbonate / graphite composite material provided by the present invention and a specific lithium ion battery preparation method is significantly higher than that of the comparative example.
[0214] Specifically, Example 2 and Example 3 are comparative experiments of Example 1. From the data in Table 1, it can be seen that in the preparation of lithium carbonate / graphite composite materials, when the organic lithium compound is adsorbed on the graphite surface for an appropriate number of times, an appropriate amount of organic lithium compound can be adsorbed on the graphite surface, which is beneficial to the subsequent improvement of the electrochemical performance of the battery.
[0215] Example 4-9 is a comparative experiment of Example 2, and the only difference between it and Example 2 is the standing temperature of the assembled lithium-ion battery in the oven. It can be seen from the data in Table 1 that when the standing temperature is 40-60°C, the electrochemical performance of the lithium-ion battery (Example 1, Example 4-7) is better. It can be seen that the standing temperature has a great influence on the cycle performance and rate performance of the lithium-ion battery. This is mainly because the standing temperature affects the reaction of lithium carbonate and the electrolyte lithium salt LiPF6. If the standing temperature is too low (below 40°C), the reaction rate of lithium carbonate and the electrolyte lithium salt LiPF6 is slow, and it is difficult to form an effective lithium fluoride coating layer. If the standing temperature is too high, although more lithium fluoride is generated, more side reactions are generated, which will affect the electrochemical performance of the battery.
[0216] Examples 10 and 11 are also comparative experiments of Example 2. The difference between the three lies in the concentration of the organic lithium compound in the aqueous solution containing the organic lithium compound used in preparing the lithium carbonate / graphite composite material. The concentration of the organic lithium compound will affect the thickness and uniformity of the lithium carbonate coating layer on the graphite surface, thereby affecting the reaction between the lithium carbonate coating layer and the electrolyte lithium salt LiPF6, and ultimately having a certain impact on the performance of the lithium ion battery.
[0217] Examples 13-15 investigate the influence of high temperature calcination temperature in the process of preparing lithium carbonate / graphite composite materials. As can be seen from the data in Table 1, the high temperature calcination temperature cannot be too high, but it cannot be too low. Only when it is within a suitable numerical range can a good technical effect be achieved. It can also be considered that the high temperature calcination temperature affects the electrochemical performance of lithium ion batteries by affecting the formation of the lithium carbonate coating layer.
[0218] Comparative Example 3 is compared with Example 2 to mainly investigate the effect of the oven standing step on the electrochemical performance of the lithium ion battery. From the data in Table 1, it can be seen that the electrochemical performance data of Comparative Example 3 is significantly lower than that of Example 2, especially the 100-cycle retention rate. This is mainly because the lithium carbonate coating layer in the lithium carbonate / graphite composite material is difficult to effectively in-situ convert into a lithium carbonate / lithium fluoride composite coating layer without oven standing, and the irreversible lithium consumption caused by the formation of the SEI film on the surface of the graphite negative electrode material cannot be alleviated.
[0219] Comparative Example 4 investigates the influence of the type of electrolyte lithium salt. Since the electrolyte lithium salt LiPF6 in the present invention reacts with the lithium carbonate of the lithium carbonate coating layer to be in-situ converted into a lithium carbonate and lithium fluoride composite coating layer, the lithium bis(fluorosulfonyl)imide used in the comparative example does not react with lithium carbonate, so the purpose of in-situ conversion cannot be achieved, and the electrochemical performance of the lithium-ion battery cannot be effectively improved.
[0220] Unlike Example 2, Comparative Example 5 adopts the traditional solid phase ball milling method to prepare the lithium carbonate / graphite composite material. The different preparation methods make the size and morphology of the obtained lithium carbonate / graphite composite material also very different. The lithium carbonate / graphite composite material prepared by the traditional solid phase ball milling method has the problem of large size and difficulty in uniformly coating the lithium carbonate on the graphite surface. The preparation method of the present invention has a simple coating process, and the obtained lithium carbonate / graphite composite material has a thin and uniform lithium carbonate coating layer coated on the graphite surface. In the subsequent lithium ion battery preparation, it can react more fully with LiPF6 for in-situ conversion, and can remain stable after subsequent charge / discharge cycles, which is beneficial to the improvement of electrochemical performance.
[0221] Unlike the present invention, Comparative Example 6 uses a traditional solid phase ball milling method to prepare a lithium carbonate / lithium fluoride / graphite composite material. When the amount of each raw material used in Comparative Example 6 (such as lithium carbonate, lithium fluoride, carbon-coated natural graphite, etc.) is basically the same as that in Example 2 of the present invention, it can be seen from the data in Table 1 that the first cycle charging specific capacity, first efficiency and 100 cycle retention rate of Comparative Example 6 are significantly lower than those of Example 2. This also fully demonstrates that the method of in-situ conversion of lithium carbonate / graphite composite materials in the present invention has obvious advantages when preparing lithium ion batteries.
[0222] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention are within the scope of protection of the pending claims of the present invention.
Claims
1. A lithium carbonate / graphite composite material, characterized in that: The invention comprises graphite and a lithium carbonate coating layer coated on the surface of the graphite.
2. The lithium carbonate / graphite composite material according to claim 1, characterized in that The particle size of the graphite is 15-20 μm; And / or, the graphite is graphite with a surface treated with carbon coating; And / or, the thickness of the lithium carbonate coating layer is 8-10 nm; And / or, the mass fraction of the lithium carbonate coating layer in the lithium carbonate / graphite composite material is 0.5-3.0%.
3. The method for preparing the lithium carbonate / graphite composite material according to claim 1 or 2, characterized in that: The following steps are involved: (a) providing an aqueous solution containing an organic lithium compound; (b) adding graphite to an aqueous solution containing an organic lithium compound, stirring and mixing to allow the organic lithium compound to be adsorbed onto the graphite surface, then performing solid-liquid separation, and drying the adsorbed graphite to obtain an organic lithium compound / graphite material; (c) calcining the organic lithium compound / graphite material at high temperature under a protective atmosphere to obtain a lithium carbonate / graphite composite material.
4. The method for preparing the lithium carbonate / graphite composite material according to claim 3, characterized in that: In step (a), the organic lithium compound comprises lithium acetate and / or lithium oxalate; And / or, in step (a), the mass concentration of the organic lithium compound in the aqueous solution containing the organic lithium compound is 1-5%; and / or, in step (b), the mass ratio of the graphite to the organic lithium compound in the aqueous solution containing the organic lithium compound is 100:(1-5); And / or, in step (b), the stirring and mixing time is 3-4 hours.
5. The method for preparing the lithium carbonate / graphite composite material according to claim 3, characterized in that: Step (b) comprises the following steps: (b1) adding graphite to an aqueous solution containing an organic lithium compound, stirring and mixing so that the organic lithium compound is adsorbed onto the surface of the graphite, to obtain a mixed solution A; (b2) subjecting the mixed solution A to solid-liquid separation to obtain adsorbed graphite; (b3) replacing the graphite with the adsorbed graphite and repeating step (b1) and step (b2) at least once, and then drying the obtained adsorbed graphite to obtain an organic lithium compound / graphite material; And / or, in step (b), the drying comprises rotary evaporation drying.
6. The method for preparing the lithium carbonate / graphite composite material according to any one of claims 3 to 5, characterized in that: In step (c), the protective atmosphere comprises argon and / or nitrogen; And / or, the high temperature calcination temperature is 600-700°C, and the high temperature calcination temperature is kept for 4-6 hours.
7. A negative electrode sheet, characterized in that: including a negative electrode active material; The negative electrode active material comprises the lithium carbonate / graphite composite material according to claim 1 or 2 or the lithium carbonate / graphite composite material prepared by the preparation method of the lithium carbonate / graphite composite material according to any one of claims 3 to 6.
8. A method for preparing a lithium ion battery, characterized in that: The following steps are involved: After assembling the positive electrode sheet, the separator and the negative electrode sheet according to claim 7, injecting an electrolyte, and then standing to allow the electrolyte to react with the negative electrode active material, so that the lithium carbonate coating layer in the lithium carbonate / graphite composite material is converted into a lithium carbonate / lithium fluoride composite coating layer, thereby obtaining a lithium ion battery; The electrolyte includes an electrolyte lithium salt and a solvent, and the electrolyte lithium salt includes LiPF6.
9. The method for preparing a lithium ion battery according to claim 8, characterized in that: The standing temperature is 40-60°C, and the standing time is 3-4 days; and / or, the solvent of the electrolyte is a carbonate solvent, including at least one of ethylene carbonate, dimethyl carbonate, diethyl carbonate or ethyl methyl carbonate; And / or, the concentration of LiPF6 in the electrolyte is 0.5-2 mol / L.
10. A lithium ion battery, characterized in that: Prepared by the preparation method of the lithium ion battery according to claim 8 or 9; The negative electrode active material in the negative electrode sheet after reacting with the electrolyte includes a lithium carbonate / lithium fluoride / graphite composite material, and the lithium carbonate / lithium fluoride / graphite composite material includes graphite and a lithium carbonate / lithium fluoride composite coating layer coated on the surface of the graphite.